How Does Global Culture Affect the Performance of Indonesian Bureaucracy? - Dian Herdiana (ELITE JOURNAL, 2023)
Culture can practically affect the bureaucracy, it can even become the identity of a bureaucracy called bureaucratic culture. The culture that forms the bureaucracy does not only come from local Indonesian culture but also global culture. This article is intended to analyze how global culture in practice affects the bureaucracy, especially the bureaucracy in carrying out its performance. The method used in this article is a descriptive method with a qualitative approach. The analysis revealed that global culture practically affects the performance of a better bureaucracy (Eu-consequences), which means that the Indonesian bureaucracy is currently oriented to achieve procedural, disciplined, professional, and responsive to public services. The global culture affects the bureaucracy either naturally through adoption by individuals in the organization, or structured through regulations regarding organizational cultural values ​that need to be practiced by individuals in the organization. Keywords: Bureaucracy, Global Culture, Performance.